Evaluation Of Antimicrobial Stewardship Programs Implementation And Outcomes In Selected Hospitals At Makkah Region, Kingdom Of Saudi Arabia - Haseeb, Abdul (2018)
Antimicrobial stewardship programs (ASPs) are collaborative efforts to optimize antimicrobial use in healthcare institutions through evidence-based quality improvement strategies. The aim of this research was to evaluate the impact of ASPs in a critical care setting for improving antimicrobial use, cost efficiency and clinical outcomes at selected hospitals in Makkah, Kingdom of Saudi Arabia (KSA). In phase one study, an exploratory survey approach was adopted to determine the presence of morbidity caused by organisms in both out and in-patients blood isolates at two Saudi hospitals.